Political budget cycles and media freedom - Veiga, Francisco José; Veiga, Linda Gonçalves; Morozumi, Atsuyoshi (Elsevier, 2017)
This paper examines the effects of elections on the conduct of central governments' fiscal policies. To do so, it uses a unique panel database that includes disaggregated spending and revenue series at the central government level for multiple countries over the 1975–2010 period. Examining political environments under which incumbent governments generate political budget cycles (PBCs), and comparing the relative importance of factors influencing cycles, we identify media freedom as the factor that plays the most critical role. This result provides a micro-foundation for rational opportunistic models for PBCs that rely on asymmetry of information about politicians' competence, and also offers a way to relate different conditioning factors of PBCs, including fiscal transparency and the maturity of democracies. Further, we show that the election-year rise in budget deficits under low media freedom is primarily driven by an increase in the current, not capital, component of public expenditure.